ERECTA signaling regulates plant immune responses via chromatin‐mediated promotion of WRKY33 binding to target genes. Issue 2 (18th February 2021) - Cai, Hanyang; Huang, Youmei; Chen, Fangqian; Liu, Liping; Chai, Mengnan; Zhang, Man; Yan, Maokai; Aslam, Mohammad; He, Qing; Qin, Yuan
Summary: The signaling pathway mediated by the receptor‐like kinase ERECTA (ER) plays important roles in plant immune responses, but the underlying mechanism is unclear. Genetic interactions between ER signaling and the chromatin remodeling complex SWR1 in the control of plant immune responses were studied. Electrophoretic mobility shift assay and yeast one‐hybrid analysis were applied to identify ER‐WRKY33 downstream components. Chromatin immunoprecipitation analyses were further investigated. In this study, we show that the chromatin remodeling complex SWR1 enhances resistance to the white mold fungus Sclerotinia sclerotiorum in Arabidopsis thaliana via a process mediated by ER signaling. We identify a series of WRKY33 target YODA DOWNSTREAM ( YDD ) genes and demonstrate that SWR1 and ER signaling are required to enrich H2A.Z histone variant and H3K4me3 histone modification at YDD s and the binding of WRKY33 to YDD promoters upon S. sclerotiorum infection. We also reveal that the binding of WRKY33 to YDD promoters in turn promotes the enrichment of H2A.Z and H3K4me3 at YDD genes, thereby forming a positive regulatory loop to activate YDD s expression. Our study reveals how H2A.Z, H3K4me3 and ER signaling mutually regulate YDD s gene expression upon pathogen infection, highlighting the critical role of chromatin structure in ER‐signaling‐mediated plant immune responses.